EFEKTIFITAS PENGGUNAAN E-LEARNING BERBASIS EDMODO TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA - Vera Dewi Kartini Ompusunggu; Nilam Sari (JURNAL CURERE, 2019)
Along with the development of technology both directly and indirectly can change someone in communicating, socializing and learning, this is a challenge for lecturers to be able to use technology optimally and to facilitate interaction with students in teaching and learning both in class and outside the classroom so that indicators in the unit of lecture events and semester learning design can be achieved. Edmodo is a social network platform for lecturers and students to share ideas, files, agenda of activities and assignments. Edmodo is designed to create lecturer and student interactions that emphasize fast communication, polling, assignments, sharing ideas, and much more. The research aims: 1) to find out whether mathematics learning using Edmodo (experimental) is better than learning without using Edmodo (conventional) on mathematical communication; 2) to find out whether students who study using Edmodo are positive towards learning mathematics. Quantitative research with quasi-experiment method, the research design used is nonequivalent control group design: providing two different treatments to two groups, namely the experimental class (Edmodo) and the control class (conventional). Quantitative data collection and analysis techniques using normality test, homogeneity test, two average similarity test, and t test. The results of the study are: 1). Learning using edmodo is better with learning without using edmodo with mathematical communication skills. 2). Students who learn to use edmodo have a positive attitude towards learning mathematics. The implication of the research is for the next researcher, using edmodo media so that maximum control is needed on students. If further research is conducted with different samples, the results shown will also be different. This can be viewed from a variety of different characteristics of students that greatly affect the ability of mathematical communication.